KUALITAS PELAYANAN PUBLIK DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PUNCAK JAYA (Public Service Quality in Department Of Population and Civil Registration Puncak Jaya Regency) - Melele Kogoya; Tommy F. Lolowang; Rine Kaunang (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this research is to analyze the quality of public services at the Population and Civil Registry Office of Puncak Jaya Regency. The sample was determined by probability sampling with simple random sampling technique as many as 11 people. Data were analyzed descriptively qualitatively in the form of frequency tables. The research results indicated that the unsatisfactory quality of service on the tangible dimension is the completeness of the computer; on the reliability dimension is the discipline of officers in providing services; the responsiveness dimension, all indicators are unsatisfactory, namely employees are slow in providing services which is marked by a discrepancy between the service schedule and the established rules, so that the completion of KTP and KK is not in accordance with the required time; on the assurance dimension, guarantees for the completion of the KTP and KK are not in accordance with the required time; and on the dimension of empathy is the persistence of employees in providing services.